A time to act and a time for restraint: Everyday sensegiving in the context of paradox. (29th May 2021) - Benbenisty, Yizhaq; Luria, Gil
Summary: Using a mixed‐methods approach, this study examines how leaders' everyday sensegiving strategies shape followers' compliance with a paradoxical use‐of‐force policy. Building on performance data derived from 41 teams and interviews with their respective team leaders, our findings point to two sensegiving strategies: practical (connecting the policy to larger organizational goals) and internalization (connecting the policy to team members' personal norms, experiences, and values). We also identified a third communication strategy, which did not involve sensegiving: bureaucratic communication (ignoring the paradox and delivering the policy). Findings show that followers deviated less from the paradoxical policy when their leaders used either of the two sensegiving strategies (internalization and practical) compared with the bureaucratic strategy. The findings shed light on the interplay between sensegiving and leadership theories that relate to the dynamics of motivating followers in contexts of paradox, particularly meaning‐based leadership.